Ruthenium‐Immobilized Periodic Mesoporous Organosilica: Synthesis, Characterization, and Catalytic Application for Selective Oxidation of Alkanes. Issue 44 (25th August 2015) - Ishito, Nobuhiro; Kobayashi, Hirokazu; Nakajima, Kiyotaka; Maegawa, Yoshifumi; Inagaki, Shinji; Hara, Kenji; Fukuoka, Atsushi
Abstract Periodic mesoporous organosilica (PMO) is a unique material that has a crystal‐like wall structure with coordination sites for metal complexes. A Ru complex, [RuCl2(CO)3]2, is successfully immobilized onto 2, 2'‐bipyridine (BPy) units of PMO to form a single‐site catalyst, which has been confirmed by various physicochemical analyses. Using NaClO as an oxidant, the Ru‐immobilized PMO oxidizes the tertiary CH bonds of adamantane to the corresponding alcohols at 57 times faster than the secondary CH bonds, thereby exhibiting remarkably high regioselectivity. Moreover, the catalyst converts cis‐decalin to cis‐9‐decalol in a 63 % yield with complete retention of the substrate stereochemistry. The Ru catalyst can be separated by simple filtration and reused without loss of the original activity and selectivity for the oxidation reactions.